2002
DOI: 10.1097/00006534-200204150-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Surgical and Nonsurgical Interventions in Relieving the Symptoms of Macromastia

Abstract: In this report, the authors evaluate the effectiveness of breast reduction in alleviating the symptoms of macromastia by comparing baseline and postoperative health status using a series of well-validated self-report instruments. The study had a prospective design with a surgical intervention group and two control groups: a hypertrophy control group with bra cup sizes D or larger and a normal control group with bra cup sizes less than D. The effectiveness of nonsurgical interventions in relieving the symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
124
0
23

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(174 citation statements)
references
References 15 publications
9
124
0
23
Order By: Relevance
“…improvement of symptoms after breast reduction surgery has been independent of breast size, resection weight, height, weight, or body mass index (5,(7)(8)(9)(10). Some studies have tried to find predictive factors for efficient surgery in breast hypertrophy, but without success (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…improvement of symptoms after breast reduction surgery has been independent of breast size, resection weight, height, weight, or body mass index (5,(7)(8)(9)(10). Some studies have tried to find predictive factors for efficient surgery in breast hypertrophy, but without success (11)(12)(13).…”
mentioning
confidence: 99%
“…Patients with smaller resection weights have an equal improvement in breast-related symptoms as patients with greater resections (10,14). Increasing number of co-morbid conditions has been noted to have a negative impact on outcome (7). In addition, previous studies have suggested a link between postoperative patient dissatisfaction and pa-…”
mentioning
confidence: 99%
“…12,13 Both of these instruments have been used in plastic surgery outcomes studies for a variety of conditions. [14][15][16][17][18][19] The SF-36 and the MBSRQ were administered at the preoperative visit to establish a baseline; it was administered again at the six-month postoperative visit to access outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…This excessive enlargement of breasts usually causes both physical and psychosocial problems [2][3][4] and could eventually affect their future. It usually occurs in girls between 8 to 16 years with rapid enlargement of breasts; hormonal studies in these individuals are normal [5][6][7].…”
Section: Introductionmentioning
confidence: 99%